High-Temperature Corrosion and Radiation Characteristics of Thermal Sprayed Molybdenum Disilicide-Based Coatings. Issue 1 (March 2016) - Weis, S; Uhlig, T; Wagner, G; Lampke, T; Bauer, W; Moldenhauer, A
Abstract : Due to their poor oxidation resistance, most metallic components of industrial furnaces can be used only under high-temperature service conditions in inert atmospheres or vacuum. The operation in oxidizing atmospheres is normally limited to temperatures up to 1200 °C. However, it is known that molybdenum disilicide shows a good oxidation resistance in the temperature range up to 1650 °C. Therefore, the aim of this work is the application of molybdenum disilicide coatings for high-temperature oxidation protection of molybdenum-based substrates. Thermal spraying of agglomerated and sintered powder was carried out by atmospheric plasma spraying (APS). Feedstock and coatings were characterized by means of optical microscopy. The high- temperature oxidation behavior was investigated by exposure tests in air at 500 °C and 1200 °C. All coatings didn't show any degradation after this exposure tests. Additionally the formation of the SiO2 protection layer on the surface of the MoSi2 -based coatings was detected by in-situ- measurements of spectral emissivities by Fourier transform infrared spectroscopy (FTIR).